Open Source Software on the Research of Extractive Adoption of Software Product Lines - Wolfart, Daniele; Assunção, Wesley Klewerton Guez; Martinez, Jabier (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2019: Anais do XVI Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2019.10349, 2019)
Beyond the main purpose of Open Source Software (OSS) to provide open industrial and personal solutions, pieces of OSS are also the subject of many research efforts. In this work we focus on OSS usage as case study subjects in the context of extractive adoption of software product lines. This research field is related to re-engineering existing system variants towards a more systematic reuse for the creation and management of a family of products. By analyzing a catalog of case studies, we provide an overview and a discussion of the current research state-of-the-practice of OSS usage across the different phases of the re-engineering process. We complement this work with the identification of available OSS tools to support this process to show, as conclusion, the healthy contribution that OSS communities are directly or indirectly making to this active research field.